UNSETTLING CONCEPTIONS OF POWER THROUGH TEACHING AND LEARNING CRITICAL REFLECTION ON SOCIAL WORK PRACTICE - Béres, Laura; Fonseka, Trehani (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2023)
Social work education is expected to offer students the opportunity to develop the skills necessary for critical self-reflection as it relates to professional practice. In this paper, we will describe how a model of critical reflection is taught and practiced within our MSW program in a Canadian School of Social Work. As a professor and student within the course, we describe our experience of engaging with the incident that the student used to learn the underlying theories and process of critical reflection. Her experience involved recognizing previously taken-for-granted conceptions of power, which she explored in her final paper for the course. We continued to critically reflect together following completion of the course, and our explorations are presented and expanded upon in this paper as an example of the potential of critical reflection, and as a reminder of the importance to continually reflect upon the complexity of power. Although we began with differing conceptions of power, we agree that power is neither solely ‘bad’ nor ‘good,’ but rather is complex, fluid, and relational. The paper provides an example of the benefits of incorporating opportunities for sustained critical reflection in social work education and concludes with implications for social work practice.